Developing a regulatory framework for laser and light treatments by non-medical practitioners in Malaysian beauty industry / Mohd Azran Hafiz Ahmad - Ahmad, Mohd Azran Hafiz (2021)
Advancement of technology has led to the introduction of laser and light treatments in the beauty industry. These operator-friendly devices are known to pose significant risk of complications to the customers. It has attracted a score of registered medical practitioners as well as non-medical practitioners to participate in the industry. Whilst the registered medical practitioners providing such services are heavily regulated, the same set of regulations are not applicable to non-medical practitioners. Current regulatory framework is found to be inadequate in governing non-medical practitioners providing such services. There is a wide regulatory loopholes in terms of academic qualifications, continuous professional development as well as the regulations of premises, facilities, and devices used by non-medical practitioners providing laser and light treatments in Malaysia. It is therefore pertinent to develop a viable regulatory framework on the subject of discussion. Such regulatory framework is deemed necessary to protect the health and safety of the customers. By adopting qualitative research method involving doctrinal and comparative analysis, a viable regulatory framework of laser and light treatments for non-medical practitioners in Malaysian beauty industry is then proposed. The proposed regulatory framework ensures a safer and higher quality of laser and light treatments in our beauty industry.